Peripheral blood monocytes as a therapeutic target for marrow stromal cells in stroke patients - Satani, Nikunj; Parsha, Kaushik; Davis, Courtney; Gee, Adrian; Olson, Scott D.; Aronowski, Jaroslaw; Savitz, Sean I. (Frontiers in Neurology, 2022)
Background Systemic administration of marrow stromal cells (MSCs) leads to the release of a broad range of factors mediating recovery in rodent stroke models. The release of these factors could depend on the various cell types within the peripheral blood as they contact systemically administered MSCs. In this study, we assessed the immunomodulatory interactions of MSCs with peripheral blood derived monocytes (Mϕ) collected from acute stroke patients. Methods Peripheral blood from stroke patients was collected at 5–7 days (N = 5) after symptom onset and from age-matched healthy controls (N = 5) using mononuclear cell preparation (CPT) tubes. After processing, plasma and other cellular fractions were removed, and Mϕ were isolated from the mononuclear fraction using CD14 microbeads. Mϕ were then either cultured alone or co-cultured with MSCs in a trans-well cell-culture system. Secretomes were analyzed after 24 h of co-cultures using a MAGPIX reader. Results Our results show that there is a higher release of IFN-γ and IL-10 from monocytes isolated from peripheral blood at day 5–7 after stroke compared with monocytes from healthy controls. In trans-well co-cultures of MSCs and monocytes isolated from stroke patients, we found statistically significant increased levels of IL-4 and MCP-1, and decreased levels of IL-6, IL-1β, and TNF-α. Addition of MSCs to monocytes increased the secretions of Fractalkine, IL-6, and MCP-1, while the secretions of TNF-α decreased, as compared to the secretions from monocytes alone. When MSCs were added to monocytes from stroke patients, they decreased the levels of IL-1β, and increased the levels of IL-10 significantly more as compared to when they were added to monocytes from control patients. Conclusion The systemic circulation of stroke patients may differentially interact with MSCs to release soluble factors integral to their paracrine mechanisms of benefit. Our study finds that the effect of MSCs on Mϕ is different on those derived from stroke patients blood as compared to healthy controls. These findings suggest immunomodulation of peripheral immune cells as a therapeutic target for MSCs in patients with acute stroke.